RELEVANSI PEMIKIRAN PENDIDIKAN IMAM AL-GHAZALI TERHADAP PENDIDIKAN AGAMA ISLAM DI SMAN 1 TANAH JAWA KECAMATAN TANAH JAWA KABUPATEN SIMALUNGUN PADA ERA MILENIAL - Pramustika, Anisyah (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2023)
Education is an effort to prepare students to be able to carry out roles that require mastery of knowledge. According to Imam Al-Ghazali, true education is a means of getting closer to Allah SWT. Education leads people to achieve happiness in this world and the hereafter, as well as a means of spreading virtue. This research aims: "To determine the relevance of Imam Al-Ghazali's educational thoughts on Islamic religious education at SMAN 1 Tanah Java in the Millennial Era." The type of research used in this research is Qualitative Research. The data sources in this research are primary data sources and secondary data sources. The primary data sources in this research are Islamic religious education subject teachers and Muslim students, while the secondary data sources in this research are literature studies, references, documentation and observations. Data collection techniques through interviews, observation and documentation. Data analysis in this research shows that the relevance of Imam Al-Ghazali's educational thoughts is very relevant to educational goals, methods and educational subjects for educators at SMAN 1 Tanah Jawa. The results of the research on Islamic religious education at SMAN 1 Tanah Jawa which are relevant to Imam Al-Ghazali's educational thinking are seen in the objectives of Islamic religious education which have the aim of emphasizing the moral education of students as a means of getting closer to Allah SWT, to achieve happiness in this world and the hereafter. It is also seen in the methods used in learning Islamic religious education as well as the educational subjects seen in teachers. And it is still less relevant to the curriculum and educational subjects seen by students.